Analisis Populasi Ternak Sapi di Kabupaten Bulukumba, Provinsi Sulawesi Selatan, Indonesia - Rusny Rusny; Muhammad Basir Paly; Andiani Andiani Andiani; Mashuri Masri; Siska Tridesianti (Faculty of Animal Husbandry, University of Mataram, 2022)
This study aims to analyze the development of beef cattle population, as well as to identify government efforts in order to develop beef cattle population in Kajang District. The study was carried out from February – August 2021 which is located in Kajang District, Bulukumba Regency, South Sulawesi Province. Quantitative data were analyzed using trend analysis, with the results of the study that there is a development of beef cattle population in Kajang District, Bulukumba Regency. For the period 2021 and 2022 shows that have been made by the development will continue to occur in the following year.